A feasibility study on UP National Engineering Center (NEC) - Tapar, Chiatanya; Venzon, Katherine S.
Established on January 27, 1978, the UP National Engineering Center (UP-NEC) is a distinct and separate unit of the University of the Philippines by virtue of the Presidential Decree 1295. Its mission to provide and sustain an expanding resource of technical expertise, solutions and information is being realized through its service offerings namely Training, Advisory and Engineering Information, all of which are geared towards national development. As with other existing technologies, NEC's current services can be developed in order to respond to its mandate with the changing of times. This study investigated its feasibility in the next five years through the analysis of the market, technical and financial, as well as the socio-economic profitability. Different sectors were investigated to determine the technical requirements of the different establishments. Current market share of NEC is estimated to be 18.66% and is expected to increase to 45% by 2016 through the different promotional strategies proposed. For the technical analysis, facilities, manpower, and production requirement were determined to know if NEC can accommodate the demand for which it is affirmative. Two additional workers will be hired under the Engineering Information Service in order to assist in the marketing activities. In the financial analysis, the commercial profitability of NEC was assessed. Based on the balance sheet, cash flow and income statement, finances were projected and have promising profit from 2012-2016. Benefits and costs were determined in the socio-profitability analysis. It was determined that the benefits well outweigh the cost of the project.